Evaluate of correlation coefficient technique for automated stitching appendicular skeleton x-ray image - โรจนอัมพวัน, ถิรวุฒิ; พฤกษ์ภัทรานนต์, พรชัย; ตัณฑนุช, สาวิตร์; อินา, นัที; ชีวกุล, จงวัฒน์ (RMUTL Engineering Journal, 2019)
This article presents the X-ray image stitching algorithm for appendicular skeleton diagnosis based on correlation coefficients. The X-ray images samples were obtained from phantom models. The proposed technique decreased processing time by filtering and reducing image size, in contrast to the old technique which used all pixel points for finding correlation coefficient. Moreover, the proposed method reduced processing time by creating rectangular frames around connected points to identify the image reference for finding correlation coefficient. The accuracy results of the correlation between radiography of upper limb and lower scapula were 97.60 and 98.22 percent.